U-PB, HF AND O ISOTOPE EVIDENCE FOR TWO EPISODES OF FLUID-ASSISTED ZIRCON GROWTH IN MARBLE-HOSTED ECLOGITES FROM THE DABIE OROGEN - Wu Y.-B.; Zheng Y.-F.; Zhao Z.-F.; Gong B.; Liu X.; Wu F.-Y. (My University, 2006)
A combined study of internal structure, U-Pb age, and Hf and O isotopes was carried out for metamorphic zircons from ultrahigh-pressure eclogite boudins enclosed in marbles from the Dabie orogen in China. CL imaging identifies two types of zircon that are metamorphically new growth and recrystallized domain, respectively. The metamorphic zircons have low Th and U contents with low Th/U ratios, yielding two groups of 206Pb/238U age at 245 ± 3 to 240 ± 2 Ma and 226 ± 4 to 223 ± 2 Ma, respectively. Anomalously high δ18O values were obtained for refractory minerals, with 9.9 to 21.4‰ for garnet and 16.9‰ for zircon. This indicates that eclogite protolith is sedimentary rocks capable of liberating aqueous fluid for zircon growth during continental subduction-zone metamorphism. Most of the zircons are characterized by very low 176Lu/177Hf ratios of 0.000001-0.000028, indicating their growth in association with garnet recrystallization. A few of them falling within the older age group have comparatively high 176Lu/177Hf ratios of 0.000192-0.000383, suggesting their growth prior to the formation of garnet in the late stage of subduction. The variations in the Lu/Hf ratios for zircons can thus be used to correlate with garnet growth during eclogite-facies metamorphism. In either case, the zircons have variable εHf (t) values for individual samples, suggesting that their protolith is heterogeneous in Hf isotope composition with localized fluid availability in the bulk processes of orogenic cycle. Nevertheless, a positive correlation exists between 206Pb/238U ages and Lu-Hf isotope ratios for the metamorphically recrystallized zircons, suggesting that eclogite-facies metamorphism in the presence of fluid has the identical effect on zircon Lu-Hf and U-Th-Pb isotopic systems. We conclude that the zircons of the older group grew in the presence of fluid during the subduction prior to the onset of peak ultrahigh-pressure metamorphism, whereas the younger zircons grew in the presence of fluid released during the initial exhumation toward high-pressure eclogite-facies regime. © 2006 Elsevier Inc. All rights reserved.